Pengembangan Karakter Cinta Tanah Air Melalui Pembelajaran Aswaja - Afifuddin Fathoni; Lestari Widodo; Moh. Syafi'i (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
The character of patriotism is an important element in national and state life, because it can foster a sense of nationalism and harmony between citizens. Therefore, patriotism character education needs to be instilled from an early age, both through classroom learning and extracurricular activities. In this context, Aswaja learning at MTs Salafiyah Siman, Lamongan, has an important role in forming patriotism character in students. This study uses a descriptive qualitative method with interview techniques as the main data source. The analysis was carried out through the process of data reduction, data presentation, and drawing conclusions, as well as data validation with triangulation and peer discussion. The results of the study showed that the Aswaja values ​​taught include aspects of history, tolerance, mutual respect, and the principles of tawassuth (moderate), tawazzun (balanced), and tasamuh (tolerant). All of these aspects support the formation of patriotism character in students.